Variation on DNA microsatellite of Holstein-Friesian dairy cows in Baturaden Dairy Cattle Breeding Center - C Sumantri; A Anggraeni; A Farajallah; D Perwitasari (Indonesian Center for Animal Research and Development (ICARD), 2007)
Eight microsatellite loci of which the locations were three on chromosome 6 (BTA6) namely CSN 3, BM 143 and BM 415; two on chromosome 9 (BTA9) namely ETH 225 and BM 4208; and three on chromosome 10 (BTA10) namely BP 31, BM 1237 and BM 888 were used to investigate genotypic variation of Holstein-Friesian (HF) dairy cows in Baturraden Dairy Cattle Breeding Centre. Research activities were carried out through some steps involving blood collection, DNA isolation, amplification on DNA fragments by polymerase chain reaction (PCR) and separation by electrophoresis with silver staining. Frequency and heterozygosity of genes under consideration were calculated. The results showed that the eight microsatellite loci exhibited a total number of 33 alleles. Locations of those alleles were five in BM 143 and BM 4208 loci; four in BM 415, CSN 3, ETH 225, BM 1237, BM 888 loci; and three in BP 31 locus. A number of 14 out of 33 alleles might be specific alleles for HF dairy cattle in Baturraden Dairy Cattle Breeding Centre. The lowest heterozygosity per locus (ĥ) was 0.6151 for BM 415 whilst the highest one was 0.7301 for BM 888. Additionally, the average heterozygosity for all loci (Ĥ) detected in this study was 0.6768. The genotype BB on locus BM 143 and AC on locus CSN-3 significantly affected (P<0.05) the estimated breeding value of milk yield of HF cows in this location. Key Words: Holstein-Friesian Cows, DNA Microsatellite, Allele, EBV of Milk Yield